Analysis of direct costs of decompressive craniectomy in victims of traumatic brain injury - Badke,Guilherme Lellis (2018)
ABSTRACT Background: Decompressive craniectomy is a procedure required in some cases of traumatic brain injury (TBI). This manuscript evaluates the direct costs and outcomes of decompressive craniectomy for TBI in a developing country and describes the epidemiological profile. Methods: A retrospective study was performed using a five-year neurosurgical database, taking a sample of patients with TBI who underwent decompressive craniectomy. Several variables were considered and a formula was developed for calculating the total cost. Results: Most patients had multiple brain lesions and the majority (69.0%) developed an infectious complication. The general mortality index was 68.8%. The total cost was R$ 2,116,960.22 (US$ 661,550.06) and the mean patient cost was R$ 66,155.00 (US$ 20,673.44). Conclusions: Decompressive craniectomy for TBI is an expensive procedure that is also associated with high morbidity and mortality. This was the first study performed in a developing country that aimed to evaluate the direct costs. Prevention measures should be a priority.